1998
DOI: 10.3109/09638289809166851
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of child disability in Saudi Arabia

Abstract: A large scale prevalence study for child disability of those under 15 years was conducted in a representative Saudi population with accurate demographic records. A 83% response rate in children of six to 15 years (1280 out of 1544 children registered) of age and a 100% response rate in children under five years (all the 1151 registered) was achieved. Thirty one children had severe impairment and 322 had minor impairment. This accounted for 3.76 per 1000 total population with major impairment and 42.8 per 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
8
2
Order By: Relevance
“…In cross tabulation (Pearson Chi-square test for independence), we found a significant difference between mothers who reported a high vs. low overall quality of life for their child by family income and cause of seizure. By family income, 94.1% (n = 48) of mothers in families with income < 5000 SAR reported that their children had a low quality of life, compared to 81.5% [22] mothers with income > 5000 to 10000 SAR (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cross tabulation (Pearson Chi-square test for independence), we found a significant difference between mothers who reported a high vs. low overall quality of life for their child by family income and cause of seizure. By family income, 94.1% (n = 48) of mothers in families with income < 5000 SAR reported that their children had a low quality of life, compared to 81.5% [22] mothers with income > 5000 to 10000 SAR (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…However, one study identified a prevalence of 6.5/1000 for Saudi Arabia [18]. The data on pediatric epilepsy are even more limited, with one study from 1998 estimating prevalence at 2.5/1000 [22]. However, more recent investigation is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, a prevalence study for children with disability less than 15 years reported 42.8 per 1000 total with minor impairment and 3.76 per 1000 total population with major impairment [ 26 ]. So, the importance of person who provides oral health care for persons with SHCN including health care professionals, caregivers, students, and parents is critical.…”
Section: Discussionmentioning
confidence: 99%
“…The role of health‐related quality of life and OHRQoL measures in supplementing clinical measures has been highlighted in the dental literature over the past decade . ‐ As authors have devised and validated measures for young children, it has been consistently shown that parents can, to some extent, serve as proxies or judges of OHRQoL . When we consider the fact that parents are considered to be apt proxies in children with chronic diseases, their importance in caring for autistic children becomes even more important.…”
Section: Discussionmentioning
confidence: 99%